2021
DOI: 10.1002/jbm.a.37175
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of NF‐κB‐induced chronic inflammation mitigates inflammatory osteolysis in the murine continuous polyethylene particle infusion model

Abstract: Wear particle‐associated bone loss (periprosthetic osteolysis) constrains the longevity of total joint arthroplasty (TJA). Wear particles induce a prolonged upregulation of nuclear factor kappa B (NF‐κB) signaling in macrophages and osteoclasts. Synthetic double‐stranded oligodeoxynucleotides (ODNs) can prevent the binding of NF‐κB to the promoter regions of targeted genes and inhibit genetic activation. We tested the hypothesis that polyethylene‐particle induced chronic inflammatory bone loss could be suppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 39 publications
1
36
0
Order By: Relevance
“…The increased pro-inflammatory M1 macrophage proportion and the decreased anti-inflammatory M2 macrophage proportion caused by cPE over a 3-week period was subsequently reduced by the local injection of MSCs and NF-κB sensing IL-4 over-expressing MSCs at harvest 3 weeks later. The increased TRAP positive osteoclast-like cell number, the lower ALP positive osteoblast-like area and BMD trend in the presence of cPE infusion further confirmed that the cPE could induce bone loss ( Lin et al, 2016 , 2017a ; Pajarinen et al, 2017 ; Utsunomiya et al, 2021a , b ). The injection of MSCs and NF-κB sensing IL-4 over-expressing MSCs reversed these findings in part.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…The increased pro-inflammatory M1 macrophage proportion and the decreased anti-inflammatory M2 macrophage proportion caused by cPE over a 3-week period was subsequently reduced by the local injection of MSCs and NF-κB sensing IL-4 over-expressing MSCs at harvest 3 weeks later. The increased TRAP positive osteoclast-like cell number, the lower ALP positive osteoblast-like area and BMD trend in the presence of cPE infusion further confirmed that the cPE could induce bone loss ( Lin et al, 2016 , 2017a ; Pajarinen et al, 2017 ; Utsunomiya et al, 2021a , b ). The injection of MSCs and NF-κB sensing IL-4 over-expressing MSCs reversed these findings in part.…”
Section: Discussionmentioning
confidence: 59%
“…is still a major an unsolved problem. We have demonstrated that local delivery of contaminated polyethylene particles (cPE) can induce acute or chronic inflammation and polarize macrophages to a pro-inflammatory M1 rather than an anti-inflammatory M2 macrophage phenotype in different in vitro and in vivo models ( Utsunomiya et al, 2021a , b ). Macrophages are the characteristic cell type involved in chronic inflammation ( Allison et al, 1978 ; Maruyama et al, 2020 ); furthermore modulation of macrophage phenotype at an appropriate time can optimize osteogenic differentiation of MSCs ( Lin et al, 2019 ) and the enhancement of the bone regeneration ( Chow et al, 2019 ; Niu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of crucial signaling pathways involved in WP-induced pro-inflammatory responses and osteolysis therefore raises the possibility that pharmacological modulation of these pathways could prevent detrimental responses to WPs in patients. A variety of drugs have displayed efficacy in preventing osteolytic responses to WPs in vivo, particularly anti-resorptive agents targeting osteoclasts, such as bisphosphonates and osteoprotegerin (OPG) [36,37], and agents targeting pro-inflammatory signaling such as IL-1β [43] or NFκB activation [48], although these were assessed in the absence of a bacterial infection. Indeed, we have previously assessed the efficacy of the bisphosphonate zoledronic acid [26] and the non-steroid anti-inflammatory drug carprofen [30] for affecting osteolytic responses to S. epidermidis infection, but found both drugs to diminish antibiotic efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Both lower limbs from each animal were collected. µCT scans were performed using a TriFoileXplore CT 120 (TriFoil Imaging, Chatsworth, CA) with 50 μm resolution ( Ueno et al, 2020 ; Utsunomiya et al, 2021a ; Utsunomiya et al, 2021b ). In the left femur (the healthy side), a 3 × 3 × 2 mm rectangular region in the center of femur was scanned ( Figure 2A ).…”
Section: Methodsmentioning
confidence: 99%